Evidence-Based Approaches to Teaching Reading in EFL Higher Education: A Systematic Review of Trends and Outcomes - Chusnul Chotimah, Ima; Mahbub, Moh. Arif; El Sulukiyyah, Ana Ahsana; Widiati, Utami; Suryati, Nunung; Anugerahwati, Mirjam (Universitas Teuku Umar, 2025)
This study provides an analysis of a systematic review of the past studies published on methods of teaching reading in English as a Foreign Language (EFL) classrooms. The analysis is based on 27 published article journals from 2014 to 2023 using e-data based: Scopus, Taylor & Francis, and Science Direct. This study is based on a Systematic Literature Review (SLR) approach. The researchers would map the articles based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The data were analyzed using content analysis. The summary of the finding is (1) publication trends and network visualization shows detailed links for mapping the status of topics that have or have not been widely explored or discussed, (2) various methods in teaching reading for EFL classrooms and the effectiveness of using those methods to enhance students’ proficiency. The finding from this SLR served as a valuable resource for educators facilitating a deeper understanding of the methods of teaching reading, the result affecting students' reading skills, and its implication for enhancing the quality of education.